2015
DOI: 10.1088/0004-637x/801/2/80
|View full text |Cite
|
Sign up to set email alerts
|

A TURNOVER IN THE GALAXY MAIN SEQUENCE OF STAR FORMATION ATM*∼ 1010MFOR REDSHIFTSz< 1.3

Abstract: The relationship between galaxy star formation rates (SFR) and stellar masses (M * ) is re-examined using a mass-selected sample of ∼62,000 star-forming galaxies at z ≤ 1.3 in the COSMOS 2-deg 2 field. Using new far-infrared photometry from Herschel-PACS and SPIRE and Spitzer-MIPS 24 µm, along with derived infrared luminosities from the NRK method based on galaxies' locations in the restframe color-color diagram (N U V − r) vs. (r − K), we are able to more accurately determine total SFRs for our complete sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

53
351
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(411 citation statements)
references
References 95 publications
53
351
7
Order By: Relevance
“…In agreement with recent results, we find that SFRs are roughly proportional to stellar mass at low masses (10 10.2 M e ), but that this trend flattens at higher masses (see also Whitaker et al 2014;Lee et al 2015;Schreiber et al 2015;Tasca et al 2015). Furthermore, although the evolution of the SFR-M * relation is still predominantly in normalization, the slope at high masses (M *  10 10.2 M e ) is also changing.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with recent results, we find that SFRs are roughly proportional to stellar mass at low masses (10 10.2 M e ), but that this trend flattens at higher masses (see also Whitaker et al 2014;Lee et al 2015;Schreiber et al 2015;Tasca et al 2015). Furthermore, although the evolution of the SFR-M * relation is still predominantly in normalization, the slope at high masses (M *  10 10.2 M e ) is also changing.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, although the evolution of the SFR-M * relation is still predominantly in normalization, the slope at high masses (M *  10 10.2 M e ) is also changing. Similar to Lee et al (2015) and Tasca et al (2015) we find that the transition mass at which this flattening occurs evolves with redshift; this is true whether or not quenched galaxies are included. Full parameterizations of the SFR-M * relation with respect to redshift, Ψ(z, M * ), for both all and star-forming galaxies are presented in Section 3.3 and shown in Figures 7 and 8.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…While the SFR-M * correlation is known to have some dispersion, in order to judge distance from the main sequence, we define it with a single line, as has been done in W11 and Bluck et al (2014). We also note that while the observed main sequence slope is known to flatten toward higher stellar mass (Whitaker et al 2012;Schreiber et al 2015;Lee et al 2015), here we extrapolate the slope derived for lower stellar mass galaxies to higher mass. We do this following the interpretation that the decrease in slope at higher stellar mass is due to the higher probability the galaxies of larger mass are already starting to quench and move off of the main sequence.…”
Section: Defining the Main Sequencementioning
confidence: 99%
“…This "bending" is more pronounced at low redshifts (e.g. Lee et al 2015;Schreiber et al 2016). The cause of this bending has not been established, but it has been suggested that it might be associated with the formation of ellipticals through environmental quenching (e.g.…”
Section: The Bending Of the Main Sequence At High M *mentioning
confidence: 99%